2022
DOI: 10.1007/s00170-022-09671-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall fracture mechanism in ultrasonic-assisted cutting of honeycomb materials

Abstract: Revealing the ultrasonic cutting mechanism of honeycomb composite is important for determining the acoustic parameters of the ultrasonic system and selecting the parameters of the cutting process. Understanding more details of the stress on the cell wall from ultrasonic vibrating tool and the conditions for cell wall breakage is essential to study the machining mechanism. According to the evolution of contact state between the straight edge cutter and the honeycomb cell wall in a cycle, the cutting force actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Jaafar et al 20 used the Hashin failure criterion to simulate the tool milling honeycomb machining process and systematically investigated the influence of cutting parameters on the formation of surface morphology. In addition, for the high-speed milling technology of honeycomb core, the researchers have carried out research on the cutting force model, 21 milling damage characteristics and suppression, 22,23 tool selection and tool wear research, fixation method, 24,25 milling process, [26][27][28] and so on. Previous studies have shown that due to the weak stiffness characteristics of honeycomb composites and the high strength and toughness of fibers, the formation of defects such as burrs, tearing, and crushing cannot be avoided when high-speed milling is used.…”
Section: Introductionmentioning
confidence: 99%
“…Jaafar et al 20 used the Hashin failure criterion to simulate the tool milling honeycomb machining process and systematically investigated the influence of cutting parameters on the formation of surface morphology. In addition, for the high-speed milling technology of honeycomb core, the researchers have carried out research on the cutting force model, 21 milling damage characteristics and suppression, 22,23 tool selection and tool wear research, fixation method, 24,25 milling process, [26][27][28] and so on. Previous studies have shown that due to the weak stiffness characteristics of honeycomb composites and the high strength and toughness of fibers, the formation of defects such as burrs, tearing, and crushing cannot be avoided when high-speed milling is used.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely applied to titanium alloys [1][2][3][4], high-temperature alloys [5][6][7][8], semiconductor wafers [9][10][11][12], engineering ceramics [13][14][15], ceramic matrix * Author to whom any correspondence should be addressed. composites [16,17], and honeycomb composites [18][19][20][21] and other difficult-to-process materials.…”
Section: Introductionmentioning
confidence: 99%